Career Decision-Making Self-Efficacy as Mediator of Parental Career Support and Vocational Identity - Pratama, Muhammad Fikri; Muttaqin, Darmawan (Universitas Ahmad Dahlan, 2024)
Previous research has found that parental support can help adolescents determine their vocational identity. However, parental support may not directly contribute to vocational identity but instead first make adolescents have career decision-making self-efficacy. This study examined the effects of career decision-making self-efficacy as a mediator in the relation between parental career support and vocational identity. The participants included 400 senior high school students aged between 15-18 with both parents and the data was analyzed through the Structural Equation Modeling (SEM). The results showed that career decision-making self-efficacy mediates between parental career support with career exploration and career commitment. These findings indicate that parental career support helps adolescents develop career decision-making self-efficacy so that adolescents can achieve an optimal vocational identity characterized by career exploration and commitment. This study found no significant effect on career reconsideration, possibly due to parental support and individual characteristics.